2019
DOI: 10.1080/17524032.2019.1664607
|View full text |Cite
|
Sign up to set email alerts
|

Powered by Immersion? Examining Effects of 360-Degree Photography on Knowledge Acquisition and Perceived Message Credibility of Climate Change News

Abstract: Research on the effects of climate change imagery has mainly focused on traditional photographs or infographics, thereby neglecting other visual presentation forms increasingly used in today's digital landscape. Hence, this study investigates how an immersive 360-degree photograph affects individuals' knowledge acquisition and perceived message credibility when being embedded in text-based climate change coverage. To isolate the modality features driving potential effects, the 360-degree photograph is contrast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 53 publications
1
7
0
Order By: Relevance
“…They assume that, in general, users are willing to engage with interactive content but only if it is crucial to the central storyline. These findings align with previous work showing that simple interactive affordances, such as clicking or swiping on an image, might eventually become too boring for users (Greussing, 2019), while complex interactive pathways are likely to overwhelm and confuse them (Bucy, 2004). Consequently, interactive data visualizations might encourage users to turn away from the visual content, seeking other information sources, such as the surrounding text, to help them understand the article content more easily and straightforwardly.…”
Section: Interactive and Animated Elements In Data Visualizations: Imsupporting
confidence: 90%
“…They assume that, in general, users are willing to engage with interactive content but only if it is crucial to the central storyline. These findings align with previous work showing that simple interactive affordances, such as clicking or swiping on an image, might eventually become too boring for users (Greussing, 2019), while complex interactive pathways are likely to overwhelm and confuse them (Bucy, 2004). Consequently, interactive data visualizations might encourage users to turn away from the visual content, seeking other information sources, such as the surrounding text, to help them understand the article content more easily and straightforwardly.…”
Section: Interactive and Animated Elements In Data Visualizations: Imsupporting
confidence: 90%
“…Feng et al’s (2019) result provided indirect support on this claim by showing that the 360-degree feature in video advertising led to greater feelings of engagement when the ad’s narrative structure was moderately complex, but not when its structure was highly complex. Greussing (2020) also found that adding a 360-degree video to text-based news was correlated with less knowledge acquisition among readers. Indeed, self-efficacy has been found to play a positive role in motivating cognitive processing when cognitive demand is high.…”
Section: Literature Reviewmentioning
confidence: 86%
“…A fair amount of research has explored how interactivity impacts users’ content perceptions with regard to fun and credibility. For example, Greussing (2020) and Fraustino et al (2018) explored whether 360-degree video increased users’ credibility perceptions of environmental or crisis communication messages. Similarly, Horning (2017) examined the effectiveness of interactivity based on how the news content was assessed as fun and credible.…”
Section: Literature Reviewmentioning
confidence: 99%
“…To advance our understanding of online engagement with science, it is important to consider the technological structures of these different online communication behaviours. As technology determines the structure of communication, technological aspects influence how people act, such as liking, sharing, tagging, and the use of algorithm-based recommendations; how they communicate, such as using emoticons, linking to other sources or addressing specific users; and how they perceive content, such as layout aspects, the presence or absence of the number of followers and likes, and the possibility of interactivity [Greussing, 2020]. The multimodality of online environments as well as particular platform vernaculars play a crucial role [Pearce et al, 2020].…”
Section: Technological Structures and Affordancesmentioning
confidence: 99%